Bone mineral density in young women of the city of São Paulo, Brazil: correlation with both collagen type I alpha 1 gene polymorphism and clinical aspects - Barros,E.R. (2002)
Osteoporosis is a multifactorial disease with great impact on morbidity and mortality mainly in postmenopausal women. Although it is recognized that factors related to life-style and habits may influence bone mass formation leading to greater or lower bone mass, more than 85% of the variation in bone mineral density (BMD) is genetically determined. The collagen type I alpha 1 (COLIA1) gene is a possible risk factor for osteoporosis. We studied a population of 220 young women from the city of São Paulo, Brazil, with respect to BMD and its correlation with both COLIA1 genotype and clinical aspects. The distribution of COLIA1 genotype SS, Ss and ss in the population studied was 73.6, 24.1 and 2.3%, respectively. No association between these genotypes and femoral or lumbar spine BMD was detected. There was a positive association between lumbar spine BMD and weight (P<0.0001), height (P<0.0156), and body mass index (BMI) (P<0.0156), and a negative association with age at menarche (P<0.0026). There was also a positive association between femoral BMD and weight (P<0.0001), height (P<0.0001), and BMI (P<0.0001), and a negative correlation with family history for osteoporosis (P<0.041). There was no association between the presence of allele s and reduced BMD. We conclude that a family history of osteoporosis and age at menarche are factors that may influence bone mass in our population.